PEMENUHAN HAK-HAK ANAK YANG BERHADAPAN DENGAN HUKUM PADA KASUS RESIDIVIS KLITIH - Dominica Shinta; Muhammad Rustamaji (Sebelas Maret University, 2023)
As individuals who are immature both physically and mentally, children are vulnerable human beings. A child has not been able to protect himself because he is not yet considered capable of being held accountable for his actions, considering that he is immature and still growing. The aim of this research is to examine the fulfillment of the rights of children who are in conflict with the law in the case of recidivist klitih in Decision Number 02/Pid.Sus-Anak/2022/PN Yyk. Children as perpetrators of crime must receive special protection and protection in accordance with the law, especially in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The results of the research study show that even though the perpetrators of criminal acts in the decision are minors who commit repeated crimes (recidivist), their rights as children who are in conflict with the law must fulfill their rights. This research is intended to provide arguments and serve as a reminder for law enforcers to fulfill the rights of children who are in conflict with the law. Keywords: Children, Children's Rights, Recidivist.